Reading and Witnessing Cage by Jade Montserrat and Webb-Ellis. Issue 2 (3rd April 2022) - Moore, Alexandra
Abstract: In 2015 Jade Montserrat and Caitlin and Anj Webb-Ellis collaborated on a series of "performance to camera" videos investigating landscapes of the North Yorkshire rural estate on which Montserrat grew up. In Cage Montserrat crouches naked within a fox trap in a dense wood. This piece situates Montserrat within the political ecology of the estate and explores her experiences of entrapment within the frames of whiteness, patriarchy, and imperial history, but that the artists' process for creation and presentation of the work aimed to exceed and start to heal those experiences.